Nociceptin Receptor Is Overexpressed in Non-small Cell Lung Cancer and Predicts Poor Prognosis - Wang, Kaiyuan; Zheng, Yu; Yang, Yinli; Wang, Jian; Li, Baihui; Wei, Feng; Zhao, Hongwei; Ren, Xiubao (Frontiers in Oncology, 2019)
Classic opioid receptors, mu (μ), delta (δ), and kappa (κ), have been reported to be expressed in non-small cell lung cancer (NSCLC) cell lines and tumor tissues and to play a role in tumor prognosis. However, the expression and role of the non-classic opioid receptor, nociceptin receptor (NOP) in cancer are unclear. Our hypothesis was that NOP was also highly expressed in NSCLC tumor tissues and this could be correlated with patients’ prognostic characters. Expression of NOP was examined in archived cancer tissues from 129 enrolled NSCLC patients by immunohistochemistry and was further analysed with the patients’ outcomes. NOP expression in NSCLC cell lines was also detected. The dataset from Kaplan-Meier Plotter was used to explore the correlation between the levels of NOP mRNA in cancerous tissue and the prognosis of NSCLC patients. Cell functional assays were performed to detect the effect of NOP activation on tumor aggressive furthers. Results showed NOP expression was highly expressed in cancer tissues and human cancer cell lines. NOP expression was not associated with patients’ opioid requirement but closely with some clinicopathological indicators which reflected the malignancy. Moreover, NOP staining level was the independent poor prognostic factor for NSCLC patients receiving lobectomy, which was further verified by determining the mRNA expression levels through the online dataset. In vitro experiments revealed that NOP activation promotes the proliferation and invasion of A549 cells via PI3K/Akt signaling pathway. We conclude that NOP is overexpressed in NSCLC and is inversely correlated with patient’s postoperative survival